Impact of climate change on water balance components in the upper Ping River Basin, Thailand - Rahmani, Bashir Ahmad; Babel, Mukand Singh; Shrestha, Sangam; Duc, Hoang Nguyen; Asian Institute of Technology Fellowship; AFG Western Basins Water Resources Management Project (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Climate change is one of the most important global environmental challenges, which affect the entire earth sy stem in terms of its impact on food production, water supply, health, livelihood, energy, etc. The intent of this research was to assess the impact of climate change on the water balance components of the upper part of the Ping River basin. Although, the historical trend analysis of the climatic and hyd rologic variables as well as the projection of the future climate from GCMs was done in this study. Monthly and annual historical maximum and minimum temperature was found to be strong significant positive trend. No monthly trend has been detected in January, February and December for precipitation da ta, but there was positive trend in March and April months. For evaporation data negative trend detected in Jan - Mar and Oct - Dec. Annual trend analysis of relative humidity showed strong significant positive trend. However there was not any specific trend i n wind speed data. Monthly streamflow trend analysis of upstream stations showed positive trend in April. Four Global Circulation Models (G CMs), namely ACCESS, CNRM - CM5, MIROC - ESM and MPI - ESM - MR under R CP 4.5 and RCP 8.5 were used to project future maximum and minimum temperature and precipitation of the basin. The linear scaling bias c orrection method was applied to remove the bias and downscale the G CMs data . Maximum and minimum temperature increase in all future perio ds related to baseline with minimum t emperature slightly higher than maximum temperature in both RCP scenarios . The maximum temp erature is increasing by 2p0(BC under RCP 4.5 and 3.5p0(BC under RCP 8.5 by 2100. The minimum temperature is increasing by 3p0(BC under RCP 4 .5 and 4p0(BC under RCP 8.5 by the end of century . Annual precipitation is expected to increase relative to baseline period in all GCMs except in ACCESS model . The impact of climate change on water balance components was quantifie d based on spatial and temporal variations using ArcSWAT. Fou r indicator which are surface runoff, evapotranspiration, groundwater recharge and water yield are considered to analyze the change in water balance components . It was found that Surface runoff and water yield are increasing under MPI model in all sub - basi ns and time periods; meanwhile decrease under ACCESS and CNRM models under RCP 8.5 . Evapotranspiration highly increases under CNRM and MIROC models ; ACCESS model also shows substantial increase under RCP 8.5 in all future periods and sub - basins. Groundwa ter recharge is expected to decrease under ACCESS and CNRM models while it increases under MIROC and MPI model in almost all sub - basinss
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Engineering in Water Engineering and Managemen
Thesis (M.Eng.) - Asian Institute of Technology, 2018
Keywords: Climatic changes -- Thailand -- Ping River Basin; Water balance (Hydrology) -- Thailand -- Ping River Basin